Metabolic flux analysis of hydrogen production network by Ethanoligenens harbinense B49 effect of product inhibition - Tang, Jing (Environmental technology, 2024)
In order to further understand the effect of product inhibition on the metabolism of hydrogen production bacteria, and to seek an effective way to increase the hydrogen yield in fermentation, a simplified metabolic model of Ethanoligenens harbinense B49 was constructed to analyse the metabolic flux under acetate and ethanol inhibition separately and to analyse the flux changes of the nodes. Based on the changes in metabolic flux distribution, Glucose 6-phosphate (G6P), Pyruvate (PYR), and Acetyl-CoA (AcCoA) were identified as key nodes of hydrogen production in the metabolic network. Robustness analysis showed that G6P was flexible, while AcCoA and PYR were weakly rigid, indicating that acetate flux could be increased by adding inhibitors or using genetic manipulation. Furthermore, releasing inhibition of acetate could effectively increase hydrogen production. These findings suggested that the addition of acetate separation in ethanol-type fermentation process is expected to improve hydrogen production, which might be a promising way to full-scale produce biohydrogen in industrial applications. Further, for the first time, we report the effect of product inhibition on key nodes in the E. harbinense B49 hydrogen production metabolism network